Diseño de prácticas lúdicas para el desarrollo de las competencias específicas en la asignatura de logística del programa de ingeniería industrial (2018)
The development of this degree project had the objective of creating the guides used by the students of industrial engineering within the logistics laboratory. In the engineering laboratories there must be a playful environment in which the students in a dynamic, pleasant and creative way can consolidate all the knowledge acquired in the theory, for this the playful guides are used in order to reinforce this knowledge. For the creation of these, it was necessary to conduct a proper investigation where the participation of the student and the support of the teachers was evidenced, with respect to the creation of these new guides, in which the opinion of the students is taken to identify which are those factors that make students feel more attracted to acquiring new knowledge, and that of teachers as support to correctly identify these learning tools. This research was carried out through surveys made to teachers and students and based on these results, guides based on a playful education were built, where the student has the opportunity to learn in a more dynamic and less monotonous way for him, so that the student will fall in love with the subject much more easily. As a result, 5 guides were created based on the most relevant topics within the logistics subject, which can be observed within this project.